Effect of Different Floral Preservatives on Vase Life of Marigold (Tagetes erecta L.) - Sharma, Asmita; Khanal, Bibek; Ojha, Sabin Raj; Khanal, Surya Prasad; Shahi, Ramba; Basnet, Manoj (Journal of the Institute of Agriculture and Animal Science, 2023)
Farmers have been growing marigold commercially but they are still lacking knowledge on procedure of postharvest handling of flowers. This has created a huge problem for those farmers since they cannot store their own produce for a longer period of time thus facing problems in marketing. In order to inform the farmers with the best means of preservation of cut flowers so that they could fetch the good market price for their product. A lab experiment to study “effect of different floral preservatives on vase life of marigold (Tagetes erecta L)” was conducted at Campus of Live Sciences, Tulsipur, Dang in a factorial Completely Randomized Design. Altogether 9 treatments were used as: Distilled Water, Silver Nitrate (100 ppm), Malic Acid (2000 ppm), Citric Acid (2000 ppm), Salicylic Acid (1000 ppm), Gibberellic acid (50 ppm), Kinetin (50 ppm), Naphthalene Acetic Acid (50 ppm), Silver Nitrate (50 ppm) + Citric Acid (1000 ppm) + Gibberellic acid (25 ppm). Results showed that the use of floral preservatives affects the parameters like flower diameter, weight, post-harvest life, blackening of petals and sepals and water uptake. It has been observed that minimum change in weight for kinetin (19.39%), minimum change in diameter for gibberellic acid (4.18%), maximum postharvest life was for gibberellic acid (14.66 days), minimum neck bending for kinetin (33%), maximum water uptake for kinetin (4.38%) and minimum blackening for growth hormones. From this experiment we can conclude that growth hormones (kinetin (50ppm) and gibberellic acid (50ppm)) are suitable for postharvest handling and storage of marigold.